IMPLEMENTASI KURIKULUM 2013 DAN PERAN MANAJER PENDIDIKAN DI SEKOLAH - Supartoyo Supartoyo (UNIVERSITAS BENGKULU, 2015)
The purpose this article is to discuss how the implementation of the curriculum 2013 and the relationship with the role of education managers in this case played by the principal. Themethod used is a literature review method. The results are: (1). Leadership principals intended to put pressure on the principal supervision competence in performing the role and duties as asupervisor, (2). The main substantive ability of principal is to make the implementation of curriculum in accordance with ideal curriculum, (3). Understanding the complete curriculum 2013will determine how curriculum could run well, and 4. Curriculum 2013 will only be a rigid document, without implementation and supervision in a factual and accurate.Keyword: implementation, curriculum 2013, role, manager, education, school